Developmental Summarization of Gleason Spiral Bevel Gear - Li Yao; Zhao Shaofu; Liu Zhiqiang (Jixie chuandong)
The spiral bevel gear is one of the most important and complicated transmission gear with large load carrying capacity and smooth transmission,it is widely applied in the aviation and spaceflight and automobile industry. The theoretic study and manufacturing level are the important symbol of one country’s mechanical industry level. The development in the field of Gleason spiral bevel gears technology including theory and design,manufacture,equipment and machine tools,material and heat treatment process is analyzed. The future developing trend in this field is also prospected.